Challenges and solutions for N-of-1 design studies in health psychology. Issue 2 (3rd April 2019) - Kwasnicka, Dominika; Inauen, Jennifer; Nieuwenboom, Wim; Nurmi, Johanna; Schneider, Annegret; Short, Camille E.; Dekkers, Tessa; Williams, A. Jess; Bierbauer, Walter; Haukkala, Ari; Picariello, Federica; Naughton, Felix
ABSTRACT: Theories of behaviour change and health behaviour change interventions are most often evaluated in between-person designs. However, behaviour change theories apply to individuals not groups and behavioural interventions ultimately aim to achieve within-person rather than between-group change. Within-person methodology, such as N-of-1 (also known as single case design), can circumvent this issue, though has multiple design-specific challenges. This paper provides a conceptual review of the challenges and potential solutions for undertaking N-of-1 studies in health psychology. Key challenges identified include participant adherence to within-person protocols, carry-over and slow onset effects, suitability of behaviour change techniques for evaluation in N-of-1 experimental studies, optimal allocation sequencing and blinding, calculating power/sample size, and choosing the most suitable analysis approach. Key solutions include involving users in study design, employing recent technologies for unobtrusive data collection and problem solving by design. Within-person designs share common methodological requirements with conventional between-person designs but require specific methodological considerations. N-of-1 evaluation designs are appropriate for many though not all types of interventions. A greater understanding of patterns of behaviours and factors influencing behaviour change at the within-person level is required to progress health psychology into a precision science. Video abstract: Supplementary Material 1.